Prediksi Jumlah Produksi Ikan Asin Menggunakan Metode Regresi Linear Sederhana - M Rajab Mudatsir; Serwin Serwin (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2022)
CV. Tirta Tenggiri produces salted fish caught from the sea or local fishermen. The production is to meet the local and outside demands of the Pohuwato District. Even though market demand for salted fish is always available, CV. Tirta Tenggiri is sometimes not able to adjust the production of salted fish with consumer demand. To obtain the information about the total production of salted fish for better development of the company in the future, predictions are made by using the simple linear regression method. The variables used include raw materials and the total demand (X) and land area as a prediction result (Y). The dataset in this study for the prediction of salted fish production takes data from 2019 to 2021. The results show that the number of salted fish to produce in May 2022 obtains a value of y = 168.53 + 24.175. The accuracy with MAPE is 0.8%. Testing the system by using a white box that has the same value of V(G) and CC, namely =2.Keywords: prediction, salted fish production, simple linear regression, White Box and Black Box Testing